Perspectives of Canadian Distance Educators on the Move to Online Learning - Ives, Cindy; Walsh, Pamela (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
Our qualitative study explored transition in seven Canadian universities—early providers of distance education that transitioned to online learning between 2002 and 2017. We interviewed 16 individuals who were involved in the design, planning, or implementation of online learning. Participants reported their universities experienced significant impacts on organizational structure and roles. Many saw an increased focus on learning and teaching. Access, revenue generation, and technology were identified as drivers of online learning; traditional learning and teaching practices were shifting; challenges experienced included resistance to change and lack of dedicated resources; and effective, visionary leadership was seen to be critically important. We propose that the roots of today’s challenges and opportunities in online learning may be found in the experiences of distance educators who were early adopters.